Identification, classification, and stress-responsive regulation of HAK family genes in poplar - Liu, Xiaojiao; Shi, Lincui; Chen, Yunyan; Wang, Jing; Liu, Aizhong; Li, Ping (Frontiers in Plant Science, 2025)
Potassium (K+) is essential for plant growth and high-affinity K+ transporters (HAKs) play vital roles in K+ uptake, translocation, and stress response. Although HAK genes have been characterized in various plants, they remain unexplored in Populus yunnanensis, an ecologically and economically important tree species in Southwest China. Here, we identified 32 HAKs in P. yunnanensis and classified them into six distinct phylogenetic groups, a structure conserved across six analyzed Populus species. Evolutionary analysis suggested that purifying selection (Ka/Ks < 1) has shaped all HAKs of the six tested poplar species with gene duplication events contributing to its expansion. All PyHAKs that were conserved contained abundant helical structures and transmembrane segments, which supported their conserved transport function. However, variations in protein and gene structure suggest potential functional diversification. Promoter analysis revealed an abundance of hormone-responsive cis-elements, and expression profiling confirmed that selected PyHAKs respond significantly to ABA, drought, heat, and osmotic stress. Furthermore, protein-protein interaction predictions, which were partially validated by yeast two-hybrid assays, indicated that PyHAK activity may be post translationally regulated via phosphorylation by calcineurin B-like (CBL) proteins. Our study provides the first comprehensive genomic and functional analysis of the HAK family in P. yunnanensis, establishing a foundation for future research on potassium regulation and stress resistance in woody plants.